Sensor databases from digital plot Chiquimula, Guatemala - Estrada Vargas, Oscar H; Ramos, Gresia Dalal; Jimenez, Daniel Ricardo; Martinez, Jesus David; Lizarazo, Miguel (2024)
In the framework of the Digital Innovation initiative, the Alliance Bioversity International -CIAT, established a digital plot at the San Carlos University, CUNORI, in Chiquimula, Guatemala. Since July 2023, meteorological, soil, and crop data have been collected there from three weather stations and a soil probe measuring temperature, soil moisture, salinity, respectively. This data is essential for understanding environmental conditions and the interactions between behavior of climate, soil, and plants in the region, and enable informed crop management decisions for data-driven decision making.